Konsepsi Hadis Mukhtalif di Kalangan Ahli Fikih dan Ahli Hadis - Arifuddin, Arifuddin; Zakka, Fathoniz (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The scholars of hadith that every second sacrifice to serve their Sunnah is like the rain that never stopped watering the earth, like trees that never stop giving fruit. Anyone who wants to learn to understand the hadith with a good understanding, it should never leave them. It is ironic if we as students hadith the end is not yet in need of them, does not depend on them but rather learn hadith from thinkers who incidentally never glorify Sunnah especially koran. Among the Sunnah which is quite difficult to understand the Sunnah that among each other mentioned hadith contradict each other or mukhtalif. For the layman who does not have a strong faith would have negative thinking and may throw accusations to the Sunnah of the Prophet Muhammad as a speaker. Therefore, the scholars of hadith not remain silent in the face of many traditions who come to our mukhtalif. Scholars of hadith and then formulate the rules that are perfect to understand the hadÃ®th mukhtalif